2021
DOI: 10.1186/s12989-021-00401-6
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of intense exercise and pollution on the airways in a murine model

Abstract: Background Exercise-induced bronchoconstriction (EIB) is a transient airway narrowing, occurring during or shortly after intensive exercise. It is highly prevalent in non-asthmatic outdoor endurance athletes suggesting an important contribution of air pollution in the development of EIB. Therefore, more research is necessary to investigate the combination of exercise and pollutants on the airways. Methods Balbc/ByJ mice were intranasally challenged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 45 publications
2
7
0
Order By: Relevance
“…In addition, in a model for exercise-induced bronchoconstriction with a running protocol of 3 to 5 weeks, no airway inflammation was present, but airway hyperreactivity was induced probably via the synthesis of cysteinyl-leukotrienes by the airway epithelium (Ueno et al, 2020). This was confirmed by previous work in our group, where in a murine 3-week running model airway hyperreactivity was observed, but no inflammation (Decaesteker et al, 2021). Airway permeability and epithelial integrity was evaluated as chlorine is an irritant and irritants can have a negative effect on airway epithelial barrier (Van Den Broucke et al, 2018).…”
Section: Discussionsupporting
confidence: 85%
“…In addition, in a model for exercise-induced bronchoconstriction with a running protocol of 3 to 5 weeks, no airway inflammation was present, but airway hyperreactivity was induced probably via the synthesis of cysteinyl-leukotrienes by the airway epithelium (Ueno et al, 2020). This was confirmed by previous work in our group, where in a murine 3-week running model airway hyperreactivity was observed, but no inflammation (Decaesteker et al, 2021). Airway permeability and epithelial integrity was evaluated as chlorine is an irritant and irritants can have a negative effect on airway epithelial barrier (Van Den Broucke et al, 2018).…”
Section: Discussionsupporting
confidence: 85%
“…Lung function was assessed using the FlexiVent FX system (SCIREQ, EMKA Technologies, Montreal, Canada), and mice were subsequently euthanized. Measurements were performed as described by Devos et al [ 63 , 64 ]. Briefly, the system was designed to measure both forced oscillations (QP3 perturbation) and forced expiration parameters and was operated with FlexiWare™ 7.6 software.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, animal models have become indispensable for studying the health effects and mechanisms of air pollution and physical activity. The study found that physical activity in a polluted environment altered airway permeability [ 50 , 51 ] and suppressed particulate-matter-induced lung inflammation and systemic inflammation in mouse models [ 52 , 53 ]. Moreover, some studies have observed that exercise can protect mice from PM 2.5 -induced cardiovascular damage [ 54 ] and improve heart rate variability [ 55 ].…”
Section: Effects Of Air Pollution and Physical Activity From Animal S...mentioning
confidence: 99%